The relationship between investment opportunity set and financing, dividend and compensation policies: evidence from Malaysia / Suhaily Hasnan - Hasnan, Suhaily Hasnan (2004)
This study provides evidence of the relationship between Investment Opportunity Set(IOS) and financing, dividend and compensation policies of companies listed on Bursa Malaysia and to identify whether the IOS theory has explanatory power in the cross sectional structure of corporate policies in Malaysia. The study was conducted using a sample of 180 companies selected from the population of 825 companies listed on both the Main Board and Second Board of Bursa Malaysia. The period of study chosen was from 1991 to 2002. For the Financing Policy Model, the results reveal that high IOS firms have lower debt and this is consistent with the Contracting Theory. On contrary, the result of Dividend Policy Model is consistent with the Signaling Theory whereby IOS is found to have a positive relationship with dividend. Further, the result of the Compensation Policy Model demonstrates that there is no statistically significant relationship between compensation policy and IOS (except for the panel data).